Monitoring Internet of Things (IoT) in Medan City MSMEs - Sembiring, Deri (International Conference on Sciences Development and Technology, 2023)
The growth of Internet of Things (IoT) technology has a significant impact on the Micro, Small, and Medium Enterprises (MSMEs) sector. This study aims to analyze and implement an IoT-based monitoring system in MSMEs in Medan City. This research involves surveys, interviews, and prototype development as the main methodologies. First, a survey was conducted to understand the level of readiness and awareness of MSMEs towards IoT technology. The findings of this survey became the foundation for designing solutions that fit the needs of the MSME sector. In-depth interviews with MSME owners provided deep insight into the challenges and opportunities faced in adopting this technology. Furthermore, based on the survey findings and interviews, a prototype IoT monitoring system was developed and implemented in several MSMEs in Medan City. The system includes connected sensors, communication modules, and a simple yet effective user interface. Evaluation results from the prototype implementation show that MSMEs in Medan City can gain significant benefits from IoT technology, including improved operational efficiency and inventory monitoring. In this context, the successful implementation illustrates the potential positive impact of IoT technology on the productivity and competitiveness of MSMEs. This research provides a comprehensive view of the challenges and opportunities of IoT implementation in the MSME sector, providing a foundation for the development of strategies and policies that support the adoption of this technology. The implications of the findings can contribute to the development of a technology-enabled MSME ecosystem in Medan City and provide insights that can be applied to similar contexts across the region.